Effects of basic endoscopic handling and care training on gastrointestinal endoscopy logistics - Mahawongkajit, Prasit; Techagumpuch, Ajjana; Auksornchat, Kharikarn (Endoscopy International Open, 2022)
Background and study aims The current practice of endoscopists is undergoing a dramatic revolution due to emerging endoscopy practices. Increasing use of gastrointestinal endoscopy has led to hospital budgets setting aside funds specifically related to damage to endoscopic instruments. Therefore, training in understanding endoscopic equipment, handling techniques, and equipment care can be helpful in addressing this issue. The aim of this study was to investigate the effects of educational courses and training about basic endoscopic handling and care in gastrointestinal endoscopic care and services.Methods A number of new endoscopists, nurses, and nurse assistants were enrolled in a course for training in basic endoscopic handling and care. Data on the type of damage, cause, cost, and timing of endoscopic repair were prospectively collected. Data from the post-training period then were compared with retrospective data from the pre-training period.Results This study demonstrated that after training, there was less damage to endoscopes, lower costs associated with it, and repair times were shorter for endoscopes than before the training course. Post-training results indicated savings of a total of $ 40,617.21 or £ 29,539.78 and 102.6 days per damaged endoscope.Conclusions Basic endoscopic handling and care training plays an important role for both endoscopists and nurses, as well as in endoscopy facilities, specifically in avoiding the nuisance of unwanted and broken endoscopes. This could be beneficial for both hospital finances and endoscopic services.